Local steroid injection in severe idiopathic granulomatous mastitis as a new first-line treatment modality with promising therapeutic efficacy - Cabioglu, Neslihan; Uras, Cihan; Mutlu, Halime; Sezgin, Derya; Emiroglu, Selman; Dulgeroglu, Onur; Yilmaz, Ravza; Tukenmez, Mustafa; Arikan, Akif Enes; Kara, Halil; Muslumanoglu, Mahmut (Frontiers in Medicine, 2023)
Background: Intralesional steroid injection has recently evolved as a novel treatment modality for localized idiopathic granulomatous mastitis (=IGM). We aimed to explore the therapeutic efficacy of local steroid injections (LSI) in patients with severe IGM.Fifty-one patients diagnosed with severe IGM were included in the study and treated with either local steroid injection (LSI)alone (n =25) or combined LSI with systemic oral steroid treatment (OST) (n = 26). The local steroid injection protocol included an intralesional triamcinolone acetonide injection into the palpable granulomas every 4-week, and topical administration of steroid-containing pomades twice a day on the affected surface of the breast. Patients with a combined LSI and OST received low-dose oral methylprednisolone (< 16 mg).Patients with LSI alone required more LSI applications than those in the combined LSI with OST group (LSI:5±2.9; vs LSI/OST:3.5 ± 2.5; p=0.080) to obtain an effective optimum therapeutic response. At a median of 12 months (range, 4-42), no difference was found in complete response rates between patients in the LSI group and the combined LSI group with OST (52% vs. 53.9%, p=0.999). However, steroid-related systemic side effects were lower in the LSI alone group (p<0.008).Local steroid injection could be considered as the first-line treatment in patients with severe IGM until a therapeutic response has been obtained either as the sole treatment modality or combined with oral steroids. Compared with systemic oral steroid therapy, local steroid administration can be considered a new treatment modality with fewer side effects.